Metal organic framework crystal material as well as preparation method and application thereof
By developing a metal organic framework crystal material composed of 2,6-two (2,4-di carboxyl phenyl) -4- (benzyl) pyridine and Zn (Ⅱ), the existing technology is solved in the low temperature environment. The problem of low temperature accuracy and resolution has achieved efficient and economic temperature measurement, and reduced production costs and risks.
Patent Information
- Application Number
- CN202411451042.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-17
AI Technical Summary
The existing temperature measurement technology has low accuracy and resolution in low temperature environments, high cost, high usage threshold, and may be toxic and produce energy consumption.
Develop a metal-organic framework crystal material, which is a periodic three-dimensional network composed of the linker 2,6-bis(2,4-dicarboxyphenyl)-4-(phenyl)pyridine and Zn(II) The structural crystal material is excited by an ordinary ultraviolet semiconductor light source, and the temperature is indicated by the afterglow decay time and color.
This material still maintains afterglow characteristics even when the particle size is small, has a short charging time, and a decay time of seconds, which reduces the cost of temperature measurement and simplifies the measurement process. It is synthesized below 120°C, reducing production costs and Danger.
Smart Images

Figure BDA0005089132650000061 
Figure BDA0005089132650000111 
Figure BDA0005089132650000112
Abstract
Description
Technical Field
[0001] The invention relates to the field of temperature measurement, and in particular to a metal organic framework crystal material and a preparation method and application thereof. Background Art
[0002] In many cases in the field of measurement and control, it is necessary to measure the temperature of the surface of the object being measured. There are currently three commonly used temperature measurement technologies: the first is to install thermocouples on the surface of the model and measure the intermittent point temperature through the thermoelectric effect; however, the thermocouple temperature measurement technology can only perform point measurements. If you want to obtain a more comprehensive temperature distribution, you need to set up many measurement points to install thermocouple equipment, but this will bring a greater burden on the economic cost and assembly work. The second is to use infrared thermal imaging technology to measure the distribution of the surface temperature of the model using the infrared radiation on the surface of the model; however, in a low temperature environment, the infrared radiation on the surface of the model is small, which will reduce the accuracy and resolution of infrared thermal imaging, and reduce the sensitivity and accuracy of temperature measurement. The third is to use temperature-sensitive paint (TSP: temperature sensitive paint), mix the temperature-sensitive probe and polymer to make a temperature-sensitive paint, and apply it on the surface of the model. The temperature-sensitive probe can convert the temperature change into the change of luminous intensity or luminous life, and measure the surface temperature distribution of the measured area through a non-contact optical measurement method. This method of measuring temperature through luminescent materials can not only achieve comprehensive temperature measurement of the model surface, but also maintain a strong signal at a lower temperature. Therefore, it is more suitable for temperature measurement applications in low-temperature environments.
[0003] However, there are some defects in the method of measuring temperature through luminescent materials: (1) Inorganic long afterglow materials are affected by trap distribution and quantum size effect. The smaller the particle size of the system, the weaker the long afterglow luminescence intensity and duration, that is, the retention of the afterglow characteristics of the material is poor at small particle size; in addition, inorganic long afterglow materials usually have deeper traps, and it takes a long time (about 3 minutes) to charge to obtain the maximum afterglow luminescence and duration. (2) Most afterglow system luminescent materials are inorganic oxide matrices doped with rare earth ions, which are expensive and may be toxic. In addition, the synthesis process may require a high temperature of more than 800℃, and the production energy consumption is high. (3) Fluorescence temperature sensors based on luminescence intensity changes are subject to systematic errors caused by the drift and fluctuation of the excitation system, reducing the measurement accuracy; while temperature sensors based on luminescence lifetime can avoid the errors caused by the light source and sample state (amount of substance, thickness, crystallinity, etc.) in principle, but measuring the luminescence lifetime (nanoseconds to milliseconds) requires expensive CCD cameras and pulsed light sources, which have high usage costs and application barriers. In fact, the light source lifetime may also be detected and mistaken for the signal from the sample, affecting the results. Summary of the invention
[0004] In view of this, the present invention provides a metal organic framework crystal material and its preparation method and application. The metal organic framework crystal material provided by the present invention still maintains the afterglow characteristics when the particle size is small, and the charging time is short; at the same time, the decay time of the metal organic framework crystal material of the present invention is in the order of seconds, and the light source only needs an ordinary ultraviolet semiconductor light source, and the camera can record the time / color of the afterglow decay as the basis for temperature judgment, which greatly reduces the temperature measurement cost and simplifies the measurement process; in addition, the metal organic framework crystal material of the present invention can be synthesized below 120°C, reducing production costs and dangers.
[0005] The invention provides a metal organic framework crystal material, wherein the crystal material is a crystal material having a periodic three-dimensional network structure formed by connecting 2,6-di(2,4-dicarboxyphenyl)-4-(phenyl)pyridine and Zn(II).
[0006] The present invention also provides a method for preparing the metal organic framework crystal material described in the above technical solution, comprising the following steps:
[0007] A) Preparation of solution:
[0008] Method 1:
[0009] Dissolving zinc salt and 2,6-di(2,4-dicarboxyphenyl)-4-(phenyl)pyridine in a solvent to obtain a solution;
[0010] Method 2:
[0011] mixing zinc salt, 2,6-bis(2,4-dicarboxyphenyl)-4-(phenyl)pyridine, a solvent and polyvinylpyrrolidone to obtain a solution;
[0012] B) heat-treating the solution obtained in step A), and then cooling and crystallizing to obtain a metal organic framework crystal material.
[0013] Preferably, in step B), the heat treatment is carried out at a temperature of 90 to 120° C. for a period of 1 to 5 days.
[0014] Preferably, in step A), the zinc salt is at least one of zinc nitrate, zinc sulfate, zinc acetate and zinc chloride.
[0015] Preferably, in the first embodiment, the molar ratio of the zinc salt to 2,6-di(2,4-dicarboxyphenyl)-4-(phenyl)pyridine is (1-5):1;
[0016] In the second method, the molar ratio of the zinc salt to 2,6-di(2,4-dicarboxyphenyl)-4-(phenyl)pyridine is (1-5):1.
[0017] Preferably, in step A), the solvent is a mixed solvent of water and N,N-dimethylformamide, or a mixed solvent of water, ethanol and N,N-dimethylformamide.
[0018] Preferably, in the mixed solvent of water and N,N-dimethylformamide, the volume ratio of water to N,N-dimethylformamide is 2:(3-8);
[0019] In the mixed solvent of water, ethanol and N,N-dimethylformamide, the volume ratio of water, ethanol and N,N-dimethylformamide is 2:1:(3-8).
[0020] Preferably, step B) specifically comprises: heat treating the solution obtained in step A), cooling it, separating the solid from the liquid to obtain crystals, and then washing and drying it to obtain the metal organic framework crystal material.
[0021] The present invention also provides an application of temperature measurement using a low-temperature long afterglow material, wherein the low-temperature long afterglow material is the metal organic framework crystal material described in the above technical solution or the metal organic framework crystal material prepared by the preparation method described in the above technical solution.
[0022] Preferably, the temperature measurement process includes:
[0023] S1. Establish statistical model:
[0024] Excite low-temperature long afterglow materials to emit light, record the afterglow decay process at different temperatures, and statistically analyze the corresponding relationship between the indicator and temperature;
[0025] Wherein, the indicator is afterglow color and / or afterglow decay time;
[0026] S2, Optical non-contact measurement:
[0027] The object to be measured is stimulated to emit light, and the obtained indication is compared with the statistical result in step S1 to obtain the corresponding temperature.
[0028] The present invention provides a metal organic framework crystal material, wherein the crystal material is a crystal material having a periodic three-dimensional network structure formed by connecting 2,6-di(2,4-dicarboxyphenyl)-4-(phenyl)pyridine and Zn(II). The present invention also provides a method for preparing the metal organic framework crystal material, and the use of the metal organic framework crystal material as a low-temperature long afterglow material for temperature measurement. The metal organic framework crystal material provided by the present invention still maintains the afterglow characteristics when the particle size is small, and the charging time is short. The best afterglow emission is obtained after 2s of ultraviolet irradiation at 310nm to 375nm, which is used for temperature measurement. At the same time, the decay time of the metal organic framework crystal material of the present invention is in the order of seconds, and the light source only needs an ordinary ultraviolet semiconductor light source. The camera can record the time / color of the afterglow decay as the basis for temperature judgment, which greatly reduces the temperature measurement cost and simplifies the measurement process; moreover, the present invention uses the above metal organic framework crystal material as a low-temperature afterglow material for temperature measurement, and the afterglow color change and duration can be used to indicate the temperature. The afterglow properties are independent of the light source system, avoiding the influence of the light source difference on the result; because the luminous interval and the afterglow interval are different, the light source can be clearly distinguished from the on and off conditions, and the afterglow color and duration can be recorded using an ordinary camera, reducing the use cost and application threshold. In addition, the metal organic framework crystal material of the present invention can be synthesized below 120°C, reducing production costs and dangers. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0030] Figure 1 A schematic diagram of an asymmetric structural unit in a metal organic framework crystal material provided by the present invention;
[0031] Figure 2 A schematic diagram of the crystal structure of the metal organic framework crystal material provided by the present invention; wherein, Figure 2 (a) and Figure 2 (b) Schematic diagrams of crystal structures at different coordinate positions;
[0032] Figure 3 is the XRD spectrum of the metal organic framework crystal material of the present invention;
[0033] Figure 4 This is a SEM image of the metal organic framework crystal material of the present invention;
[0034] Figure 5This is a graph showing the change in afterglow decay time of the metal organic framework crystal material of the present invention under 375nm ultraviolet light with different charging times;
[0035] Figure 6 is a scanning diagram of the afterglow decay dynamics of the metal organic framework crystal material of the present invention; wherein, Figure Ⅰ The graph of the luminous intensity changing with time in the charging stage is shown in Figure 2. Figure II is a schematic diagram of the afterglow decay intensity changing with time;
[0036] Figure 7 This is the afterglow decay diagram of the metal organic framework crystal material of the present invention at a temperature of 80 to 260 K;
[0037] Figure 8 Schematic diagram of the relationship between the afterglow color and temperature change of the metal organic framework crystal material of the present invention; wherein, Figure 8 (a) is a schematic diagram of afterglow color at different temperatures. Figure 8 (b) is the normalized afterglow luminescence spectrum at 80-200K. Figure 8 (c) is a schematic diagram of the maximum emission wavelength of the afterglow corresponding to the temperature of 80 to 200 K;
[0038] Fig. 9 Schematic diagram of the relationship between the afterglow decay time and temperature change of the metal organic framework crystal material of the present invention; wherein, Fig. 9 (a) is the afterglow decay curve after charging for 5 minutes at a temperature of 80-260K; Fig. 9 (b) is a statistical graph showing the time required for the afterglow intensity to reach 2%, 1%, 0.5%, 0.2% of the maximum luminous intensity and to coincide with the background signal at temperatures of 80K to 260K; Fig. 9 (c) is a statistical graph of the afterglow decay percentage at 0.2s, 0.4s, 0.6s, 0.8s and 1s after the irradiation light source is turned off at a temperature of 80-260K;
[0039] Fig.10 This is the afterglow spectrum of the metal organic framework crystal material of the present invention measured by a fiber optic spectrometer at 80K. DETAILED DESCRIPTION
[0040] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0041] As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items.
[0042] Herein, when it comes to numerical ranges, unless otherwise specified, the numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0043] In this article, when referring to the unit of a data range, if there is a unit only after the right endpoint, it means that the units of the left and right endpoints are the same. For example, 90~120℃ means that the units of the left endpoint "90" and the right endpoint "120" are both ℃.
[0044] Only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and likewise any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.
[0045] The invention provides a metal organic framework crystal material, wherein the crystal material is a crystal material having a periodic three-dimensional network structure formed by connecting 2,6-di(2,4-dicarboxyphenyl)-4-(phenyl)pyridine and Zn(II).
[0046] Metal-organic framework crystal materials refer to crystal materials with a periodic three-dimensional network structure formed by connecting organic ligands (or linkers) with metal ions / metal clusters. In the present invention, the linker in the metal-organic framework crystal material is 2,6-di(2,4-dicarboxyphenyl)-4-(phenyl)pyridine, and its structure is shown in formula (1). There is no special restriction on its source, and it can be a commercial product, such as that provided by Jinan Henghua Technology Co., Ltd. In the present invention, the metal in the metal-organic framework crystal material is Zn(Ⅱ); Zn(Ⅱ) indicates that the valence of zinc in the compound is +2. The framework crystal material is a three-dimensional network structure formed by connecting metal ions with a linker according to a certain structure, in which the asymmetric structural units such as Figure 1 Its crystal structure is shown in Figure 2 shown.
[0047]
[0048] In the present invention, the crystal structure of the metal organic framework crystal material is as follows: monoclinic system; space group is C2 / c; unit cell parameters are: β=91(1)°, α=γ=90°, Z=190.
[0049] In the present invention, the metal organic framework crystal material may also contain solvent molecules. In the preparation process of the crystal material, a solvent is used. After the crystal material is synthesized, it will be dried, and the solvent attached to its surface can be almost ignored. In addition, there may be solvent participating in the crystal material. Specifically, part of the solvent acts as a guest molecule and is randomly distributed in the pores of the framework material, while the other part participates in the coordination with the unsaturated Zn (part of it evaporates and separates after drying, and the exact position and quantity cannot be determined). Therefore, in the present invention, the chemical formula of the metal organic framework crystal material can be expressed by formula (2): C 54+3y H 26+2x+7y N 2+y O 16+x+y Zn3 formula (2), where x≥0, y≥0; x, y are determined by the solvent molecules that may exist in the crystal material. They are randomly distributed in the crystal and are related to factors such as the synthesis batch, storage environment and time. They are difficult to quantify accurately and have little effect on the material properties. Therefore, C 54 H 26 N2O 16 Simplified representation of Zn3.
[0050] The present invention also provides a method for preparing the metal organic framework crystal material described in the above technical solution, comprising the following steps:
[0051] A) Preparation of solution:
[0052] Method 1:
[0053] Dissolving zinc salt and 2,6-di(2,4-dicarboxyphenyl)-4-(phenyl)pyridine in a solvent to obtain a solution;
[0054] Method 2:
[0055] mixing zinc salt, 2,6-bis(2,4-dicarboxyphenyl)-4-(phenyl)pyridine, a solvent and polyvinylpyrrolidone to obtain a solution;
[0056] B) heat-treating the solution obtained in step A), and then cooling and crystallizing to obtain a metal organic framework crystal material.
[0057] [About Step A]:
[0058] Method 1:
[0059] Zinc salt and 2,6-di(2,4-dicarboxyphenyl)-4-(phenyl)pyridine are dissolved in a solvent to obtain a solution.
[0060] In the present invention, the zinc salt is preferably at least one of zinc nitrate, zinc sulfate, zinc acetate and zinc chloride, and more preferably zinc nitrate. Among them, the zinc nitrate is preferably Zn(NO3)3·6H2O.
[0061] In the present invention, the structure of the 2,6-di(2,4-dicarboxyphenyl)-4-(phenyl)pyridine is as shown in formula (1) (see above for details).
[0062] In the present invention, the molar ratio of the zinc salt to 2,6-di(2,4-dicarboxyphenyl)-4-(phenyl)pyridine is preferably (1-5):1, specifically 1:1, 2:1, 3:1, 4:1, 5:1.
[0063] In the present invention, the solvent is preferably a mixed solvent of water and N,N-dimethylformamide, or a mixed solvent of water, ethanol and N,N-dimethylformamide. Among them, in the mixed solvent of water and N,N-dimethylformamide, the volume ratio of water to N,N-dimethylformamide is preferably 2: (3-8), specifically 2: 3, 2: 4, 2: 5, 2: 6, 2: 7, 2: 8. In the mixed solvent of water, ethanol and N,N-dimethylformamide, the volume ratio of water, ethanol and N,N-dimethylformamide is preferably 2: 1: (3-8), specifically 2: 1: 3, 2: 1: 4, 2: 1: 5, 2: 1: 6, 2: 1: 7, 2: 1: 8.
[0064] In the present invention, the ratio of the reaction raw materials (i.e., zinc salt, 2,6-di(2,4-dicarboxyphenyl)-4-(phenyl)pyridine) to the solvent is not particularly limited, as long as the above raw materials can be fully and evenly dissolved. Specifically, the ratio of the zinc salt to the solvent is preferably 1 mmol: (10 to 100) mL.
[0065] In the present invention, the dissolution temperature of zinc salt and 2,6-di(2,4-dicarboxyphenyl)-4-(phenyl)pyridine in a solvent is not particularly limited and can be carried out at room temperature, specifically 15 to 25° C. The raw materials and the solvent are uniformly mixed until completely dissolved to obtain a solution.
[0066] Method 2:
[0067] Zinc salt, 2,6-bis(2,4-dicarboxyphenyl)-4-(phenyl)pyridine, a solvent and polyvinylpyrrolidone are mixed to obtain a solution.
[0068] In the present invention, the zinc salt is preferably at least one of zinc nitrate, zinc sulfate, zinc acetate and zinc chloride, and more preferably zinc nitrate. Among them, the zinc nitrate is preferably Zn(NO3)3·6H2O.
[0069] In the present invention, the structure of the 2,6-di(2,4-dicarboxyphenyl)-4-(phenyl)pyridine is as shown in formula (1) (see above for details).
[0070] In the present invention, the molar ratio of the zinc salt to 2,6-di(2,4-dicarboxyphenyl)-4-(phenyl)pyridine is preferably (1-5):1, specifically 1:1, 2:1, 3:1, 4:1, 5:1.
[0071] In the present invention, the solvent is preferably a mixed solvent of water and N,N-dimethylformamide, or a mixed solvent of water, ethanol and N,N-dimethylformamide. Among them, in the mixed solvent of water and N,N-dimethylformamide, the volume ratio of water to N,N-dimethylformamide is preferably 2: (3-8), specifically 2: 3, 2: 4, 2: 5, 2: 6, 2: 7, 2: 8. In the mixed solvent of water, ethanol and N,N-dimethylformamide, the volume ratio of water, ethanol and N,N-dimethylformamide is preferably 2: 1: (3-8), specifically 2: 1: 3, 2: 1: 4, 2: 1: 5, 2: 1: 6, 2: 1: 7, 2: 1: 8.
[0072] In the present invention, the ratio of the reaction raw materials (i.e., zinc salt, 2,6-di(2,4-dicarboxyphenyl)-4-(phenyl)pyridine) to the solvent is not particularly limited, as long as the above raw materials can be fully and evenly dissolved. Specifically, the ratio of the zinc salt to the solvent is preferably 1 mmol: (10-100) mL, specifically 0.2 mmol: 8 mL.
[0073] In the present invention, the ratio of the zinc salt to polyvinyl pyrrolidone is preferably 0.05 mol: (30-60) mg, more preferably 0.05 mol: 50 mg. The introduction of polyvinyl pyrrolidone in the present invention can improve the crystal morphology and make the crystal more uniform.
[0074] In the present invention, the temperature for mixing and dissolving the zinc salt, 2,6-di(2,4-dicarboxyphenyl)-4-(phenyl)pyridine, solvent and polyvinylpyrrolidone is not particularly limited and can be carried out at room temperature, specifically 15 to 25° C. After the above materials are mixed uniformly until they are completely dissolved, a solution is obtained.
[0075] [About step B]:
[0076] B) heat-treating the solution obtained in step A), and then cooling and crystallizing to obtain a metal organic framework crystal material.
[0077] In the present invention, the temperature of the heat treatment is preferably 90-120°C, specifically 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, and more preferably 100°C. The time of the heat treatment is preferably 1-5 days, specifically 1 day, 2 days, 3 days, 4 days, 5 days, and more preferably 3 days. The first method of the above heat treatment is: in a high temperature and high pressure reactor; specifically, after the solution is obtained in step A), it is loaded into a high temperature and high pressure reactor and kept constant temperature for the above time at the above heat treatment temperature. For the above first heat treatment method, the heat treatment time is more preferably 2-5 days. The second method of the above heat treatment is: heating and reflux; specifically, after the solution is obtained in step A), a reflux device is connected and heated and refluxed. In the above second heat treatment method, it is preferred to add a stirring magnet to the solution and heat the reaction while stirring. For the above second treatment method, the heat treatment time is more preferably 24h-48h.
[0078] After the above heat treatment, 2,6-bis(2,4-dicarboxyphenyl)-4-(phenyl)pyridine reacts with zinc salt, and 2,6-bis(2,4-dicarboxyphenyl)-4-(phenyl)pyridine and Zn(Ⅱ) are connected to form a crystal material with a periodic three-dimensional network structure.
[0079] In the present invention, after the above-mentioned heat treatment, cooling and crystallization are carried out. Wherein, the cooling is preferably cooling at room temperature, specifically 15 to 25°C. During the heat treatment and cooling process, crystallization gradually occurs to obtain a solution containing crystals. Afterwards, solid-liquid separation is performed to obtain crystals. Wherein, the method of solid-liquid separation is not particularly limited, and it can be a conventional method in the field, such as filtration. In the present invention, after obtaining the crystals, washing and drying are preferably performed. Wherein, the solvent used for the washing can be water and / or a volatile organic solvent. The drying is preferably vacuum drying. The drying temperature is preferably 60 to 90°C, specifically 60°C, 70°C, 80°C, 90°C, and more preferably 80°C. The drying time is preferably 1 to 3h, specifically 1h, 2h, 3h, and more preferably 2h. After the above-mentioned treatment, a metal organic framework crystal material is obtained. The asymmetric structural unit in the obtained metal organic framework crystal material is such as Figure 1 The crystal structure of the obtained metal organic framework crystal material is shown in Figure 2 shown.
[0080] The present invention also provides an application of temperature measurement using a low-temperature long afterglow material, wherein the low-temperature long afterglow material is the metal organic framework crystal material described in the above technical solution or the metal organic framework crystal material prepared by the preparation method described in the above technical solution.
[0081] In the present invention, preferably, the temperature measurement process includes:
[0082] S1. Establish statistical model:
[0083] Excite low-temperature long afterglow materials to emit light, record the afterglow decay process at different temperatures, and statistically analyze the corresponding relationship between the indicator and temperature;
[0084] Wherein, the indicator is afterglow color and / or afterglow decay time;
[0085] S2, Optical non-contact measurement:
[0086] The object to be measured is stimulated to emit light, and the obtained indication is compared with the statistical result in step S1 to obtain the corresponding temperature.
[0087] Regarding step S1:
[0088] In the present invention, the method of exciting the low-temperature long afterglow material to emit light is preferably ultraviolet irradiation. The afterglow phenomenon of the metal organic framework crystal material provided by the present invention can be observed after being irradiated by a 310nm / 365nm / 375nm near-ultraviolet lamp for 2s in a low-temperature environment, a CCD fiber optic spectrometer can measure the afterglow spectrum, and a research fluorescence spectrometer and a camera can observe the afterglow decay time.
[0089] In the present invention, the afterglow decay process is recorded at different temperatures. The recording medium may be a spectrometer or a camera. The different temperatures are preferably 80-260K.
[0090] In the present invention, when the corresponding relationship between the indicator and the temperature is statistically analyzed, the selected indicator is preferably the afterglow color and / or the afterglow decay time. That is, the afterglow decay process is recorded at different temperatures, and the change of the indicator (afterglow color and / or decay time) as the temperature changes is statistically analyzed. For example, the metal organic framework crystal material of the present invention can be observed to emit green afterglow after irradiation with 375nm ultraviolet light for 2s at 80K, and the spectrum is a broadband emission peak at 520nm, and the afterglow duration is about 6 to 7s; the afterglow decay process is recorded with a camera at 80 to 260K, and it can be observed that as the temperature increases from 80K to 260K, the afterglow decay time is shortened from about 7s to within 0.5s, and the afterglow color also changes from green to yellow. Therefore, both the decay time and the color can indicate the temperature change. The present invention uses the afterglow color and / or the afterglow decay time as the indicator, and statistically analyzes the corresponding relationship between the temperature and the above-mentioned indicator, and proposes a temperature measurement method based on the afterglow decay time / afterglow color.
[0091] Regarding step S2:
[0092] After the statistical model is established in step S1, actual temperature measurement is performed. Specifically, the object to be measured is stimulated to emit light, and an indication is obtained (specifically, the afterglow decay is recorded to obtain an indication of the afterglow color and / or afterglow decay time), and the obtained indication is compared with the statistical result of step S1 to obtain the corresponding temperature, thereby realizing the temperature measurement of the object.
[0093] It can be seen that the present invention proposes a temperature measurement method based on afterglow decay time / afterglow color. Among them, the temperature measurement method based on afterglow decay time proposes two temperature measurement strategies: 1. Counting the time required for afterglow intensity to decay to a certain proportion at different temperatures. 2. Counting the percentage of afterglow intensity decay after the light source is turned off for a certain period of time at different temperatures. The above two statistical results are as follows: Fig. 9 As shown in Figure 1-2, by calculating the time required for the afterglow to decay to a fixed percentage, or the afterglow decay percentage at a fixed time, and comparing it with the statistical test results, the ambient temperature (low temperature environment) can be optically non-contact measured.
[0094] Table 1: Statistics of the time required for the afterglow signal to decay to 2%, 1%, 0.5%, and 0.2% at different temperatures
[0095]
[0096] Table 2: Statistics of the attenuation percentage of the afterglow signal after turning off the light source for 0.2s, 0.4s, 0.6s, 0.8s, and 1s at different temperatures
[0097]
[0098] The temperature measurement method of the present invention can perform optical non-contact measurement on the ambient temperature (low temperature environment), and the temperature of the low temperature environment can be 80-260K.
[0099] Compared with the prior art, the present invention has the following beneficial effects:
[0100] 1. In the prior art, inorganic long afterglow materials are affected by trap distribution and quantum size effect. The smaller the particle size of the system, the weaker the long afterglow luminescence intensity and duration. However, the metal organic framework crystal material provided by the present invention still maintains the afterglow characteristics when the particle size is small. In the prior art, inorganic long afterglow materials usually have deeper traps and require a long time (about 3 minutes) to charge to obtain the maximum afterglow luminescence and duration. However, the metal organic framework crystal material provided by the present invention has a shorter charging time, and the best afterglow emission is obtained after 2 seconds of 310nm~375nm ultraviolet irradiation, which is used for temperature measurement.
[0101] 2. In the prior art, most afterglow systems are inorganic oxide matrices doped with rare earth ions, which are expensive and may be toxic; and the synthesis process may require a high temperature of more than 800°C, which consumes a lot of energy. The present invention uses organic ligands and cheap metal zinc to synthesize at less than 120°C, reducing production costs and dangers.
[0102] 3. In the prior art, when using afterglow materials to measure temperature, the fluorescence temperature sensor based on the change of luminous intensity is subject to drift and fluctuation of the excitation system, causing system errors and reducing the measurement accuracy; the temperature sensor based on luminescence lifetime can avoid the errors caused by the light source and sample state (amount of substance, thickness, crystallinity, etc.) in principle, but the measurement of luminescence lifetime (nanoseconds to milliseconds) requires the use of expensive CCD cameras and pulsed light sources, and in fact the light source lifetime may also be detected and mistaken for a signal from the sample. The present invention uses afterglow color changes and duration to indicate temperature, and the afterglow properties are independent of the light source system, avoiding the influence of the light source on the results; because the luminous interval and the afterglow interval are different, the light source can be clearly distinguished from the on and off conditions, and the afterglow color and duration can be recorded using an ordinary camera, reducing the use cost and application threshold. In general, the present invention uses afterglow materials with a decay time of seconds, and the light source only needs an ordinary ultraviolet semiconductor light source. The camera can record the time / color of the afterglow decay as the basis for temperature judgment, which greatly reduces the temperature measurement cost and simplifies the measurement process.
[0103] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.
[0104] Example 1
[0105] 1. Preparation of metal organic framework crystal materials
[0106] A) Zn(NO3)3·6H2O and 2,6-di(2,4-dicarboxyphenyl)-4-(phenyl)pyridine were mixed in a molar ratio of 4:1 and dissolved in a mixed solvent of water-ethanol-N,N-dimethylformamide (v / v / v=2 / 1 / 5), and mixed evenly until completely dissolved to obtain a solution.
[0107] B) The solution was sealed in a high-temperature and high-pressure reactor, placed in an oven and kept at 100°C for 3 days, cooled to room temperature and taken out, filtered to obtain a flake, aggregated crystalline sample. Then, it was washed with water and ethanol for 3 times, vacuum dried at 80°C for 2 hours, and then taken out to obtain 8.5 mg of light yellow / yellow-green crystals.
[0108] 2. Characterization and testing
[0109] (1) XRD characterization
[0110] The crystal material obtained in Example 1 was characterized by X-ray diffraction, and the results were as follows: Figure 3 shown.
[0111] (2) SEM characterization
[0112] The crystal material obtained in Example 1 was characterized by SEM, and the results were as follows: Figure 4 As shown, it can be seen that the average particle size of the obtained crystalline material is less than 5 μm.
[0113] (3) Charging time test and afterglow decay dynamics scan
[0114] The afterglow decay of the crystal material obtained in Example 1 under 375nm ultraviolet light with different charging times is as follows: Figure 5 As shown in the figure, it can be seen that when the charging time is 2s to 5min, the afterglow decay time changes little. Figure 6 Insert Figure II This indicates that the luminous intensity reaches its maximum value 2s after the start of charging, so the minimum charging time is 2s.
[0115] The crystal material obtained in Example 1 was subjected to a scanning test of afterglow decay dynamics. The results are as follows: Figure 6 As shown in the figure, it can be seen that the luminous intensity at 500nm is normalized after 365nm ultraviolet light irradiation at 80K temperature for 3min. Figure Ⅰ The fitting curve shows that the afterglow decay conforms to the law of bimolecular ionization recombination. Figure II It shows that under ultraviolet irradiation, the excited state undergoes ionization, i.e., the charging process, which reaches a maximum in 1s to 1.5s. In addition, the crystal material of the present invention can be observed to emit green afterglow after irradiation with 375nm ultraviolet light for 30s at 80K, with a broadband emission peak at 500nm to 520nm, a spectrum covering 420nm-700nm, and an afterglow duration of about 6 to 7s. Fig.10 shown.
[0116] From (2)-(3) above, it can be seen that the crystal material obtained by the present invention has a small particle size (average particle size is less than 5 μm); at 80K, green afterglow can be observed after 375nm ultraviolet light irradiation for 30s, the spectrum is a broadband emission peak at 500nm-520nm, the spectrum covers 420nm-700nm, and the afterglow duration is about 6-7s, which proves that the metal organic framework crystal material provided by the present invention still maintains the afterglow characteristics when the particle size is small. In addition, the metal organic framework crystal material provided by the present invention has a short charging time, and the best afterglow emission is obtained after 2s of 310nm-375nm ultraviolet irradiation.
[0117] (4) Afterglow decay test
[0118] The afterglow decay phenomenon of the crystal material obtained in Example 1 at a temperature of 80 to 260 K was recorded with a camera. The results are as follows: Figure 7 As shown in the figure, it can be seen that as the temperature increases (from 80K to 260K), the afterglow decay time shortens (from about 7s to within 0.5s), and the afterglow color changes (gradually from green to yellow). Therefore, according to the corresponding relationship between temperature and afterglow decay time / color, a temperature measurement method based on afterglow decay time / color is proposed.
[0119] (5) Afterglow color indication temperature measurement
[0120] The afterglow color and temperature change of the crystal material obtained in Example 1 were investigated, and the results were as follows: Figure 8 As shown, Figure 8 (a) is a schematic diagram of afterglow color at different temperatures. Figure 8 (b) is the normalized afterglow luminescence spectrum at 80-200K. Figure 8 (c) is a schematic diagram of the maximum emission wavelength of the afterglow corresponding to the temperature of 80-200 K. It can be seen that the spectrum of the afterglow red-shifts with the increase of temperature, the wavelength becomes longer, and the luminescent color gradually changes from green to yellow (the color of the afterglow gradually changes from green at 80K-140K to yellow-green at 140K-180K, and turns to yellow when the temperature rises to 180K-260K). Based on this, the approximate range of temperature can be intuitively judged based on the color of the afterglow at a certain temperature. Figure 8 (b)-(c) are the afterglow spectra measured at different temperatures and the corresponding relationship between the maximum emission wavelength and temperature. The temperature can be measured based on the maximum emission wavelength or color change of the afterglow.
[0121] (6) Afterglow decay time indication temperature measurement
[0122] The afterglow decay time and temperature change of the crystal material obtained in Example 1 were investigated, and the results are as follows: Fig. 9 As shown, Fig. 9 (a) is the afterglow decay curve after charging for 5 minutes at 80-260K. Fig. 9 (b) is a statistical graph of the time required for the afterglow intensity to reach 2%, 1%, 0.5%, 0.2% of the maximum luminous intensity and to coincide with the background signal at temperatures of 80K to 260K (see Table 1 above for statistical data). Fig. 9 (c) is a statistical chart of the afterglow decay percentage at 0.2s, 0.4s, 0.6s, 0.8s and 1s after the irradiation light source is turned off at a temperature of 80-260K (see Table 2 above for statistical data). Fig. 9(a) shows the afterglow decay curve after the material is charged for 5 minutes at different temperatures. The time from when the light source is turned off to when the afterglow signal and the background (Black) completely overlap can be considered as the afterglow decay time. For example, the afterglow decay time is 6.36s at 90K and 5.44s at 100K. The time from when the light source is turned off to when the afterglow brightness cannot be observed is considered as the decay time. The shorter the photo interval, the higher the measurement accuracy. After irradiating with a 375nm ultraviolet light source for 3 minutes at a certain temperature, take photos and record the afterglow of the sample at regular intervals. The shorter the camera photo interval, the higher the measurement accuracy. Alternatively, the video function can also record the afterglow decay process. By comparing the decay time and afterglow color with the experimental data, the temperature can be measured. It can be seen that by calculating the time required for the afterglow to decay to a fixed percentage, or the afterglow decay percentage at a fixed time, and comparing it with the statistical experimental results, the ambient temperature (low temperature environment) can be optically non-contact measured.
[0123] Example 2
[0124] A) Zn(NO3)3·6H2O and 2,6-di(2,4-dicarboxyphenyl)-4-(phenyl)pyridine were mixed in a molar ratio of 1:1, dissolved in a mixed solvent of water-ethanol-N,N-dimethylformamide (v / v / v=2 / 1 / 5), and mixed evenly until completely dissolved to obtain a solution.
[0125] B) The solution was sealed in a high-temperature and high-pressure reactor, placed in an oven and kept at a constant temperature of 100°C for 3 days, cooled to room temperature, taken out, and filtered to obtain a flaky, aggregated crystalline sample. Then, it was washed with water and ethanol three times, vacuum dried at 80°C for 2 hours, and then taken out to obtain 52.2 mg of light yellow / yellow-green crystals.
[0126] Example 3
[0127] A) Zn(NO3)3·6H2O and 2,6-di(2,4-dicarboxyphenyl)-4-(phenyl)pyridine were mixed in a molar ratio of 2:1, dissolved in a mixed solvent of water-ethanol-N,N-dimethylformamide (v / v / v=2 / 1 / 5), and mixed evenly until completely dissolved to obtain a solution.
[0128] B) The solution was sealed in a high-temperature and high-pressure reactor, placed in an oven and kept at a constant temperature of 100°C for 3 days, cooled to room temperature and taken out, and filtered to obtain a flaky and aggregated crystalline sample. Then, it was washed with water and ethanol for 3 times, vacuum dried at 80°C for 2 hours, and then taken out to obtain 29.8 mg of light yellow / yellow-green crystals.
[0129] Example 4
[0130] A) Zn(NO3)3·6H2O and 2,6-di(2,4-dicarboxyphenyl)-4-(phenyl)pyridine were mixed in a molar ratio of 3:1, dissolved in a mixed solvent of water-ethanol-N,N-dimethylformamide (v / v / v=2 / 1 / 5), and mixed evenly until completely dissolved to obtain a solution.
[0131] B) The solution was sealed in a high-temperature and high-pressure reactor, placed in an oven and kept at a constant temperature of 100°C for 3 days, cooled to room temperature and taken out, and filtered to obtain a flaky and aggregated crystalline sample. Then, it was washed with water and ethanol for 3 times, vacuum dried at 80°C for 2 hours, and then taken out to obtain 15.6 mg of light yellow / yellow-green crystals.
[0132] Example 5
[0133] A) Zn(NO3)3·6H2O and 2,6-di(2,4-dicarboxyphenyl)-4-(phenyl)pyridine were mixed in a molar ratio of 4:1 and dissolved in a mixed solvent of water and N,N-dimethylformamide (v / v=2 / 5), and mixed evenly until completely dissolved to obtain a solution.
[0134] B) The solution was sealed in a high-temperature and high-pressure reactor, placed in an oven and kept at a constant temperature of 100°C for 3 days, cooled to room temperature and taken out, and filtered to obtain a flaky and aggregated crystalline sample. Then, it was washed with water and ethanol for 3 times, vacuum dried at 80°C for 2 hours, and then taken out to obtain 7.2 mg of light yellow / yellow-green crystals.
[0135] Example 6
[0136] A) Zn(NO3)3·6H2O and 2,6-di(2,4-dicarboxyphenyl)-4-(phenyl)pyridine were mixed in a molar ratio of 5:1, dissolved in a mixed solvent of water-ethanol-N,N-dimethylformamide (v / v / v=2 / 1 / 5), and mixed evenly until completely dissolved to obtain a solution.
[0137] B) The solution was sealed in a high-temperature and high-pressure reactor, placed in an oven and kept at a constant temperature of 100°C for 3 days, cooled to room temperature and taken out, and filtered to obtain a flaky and aggregated crystalline sample. Then, it was washed with water and ethanol three times, vacuum dried at 80°C for 2 hours, and then taken out to obtain 4.1 mg of light yellow / yellow-green crystals.
[0138] Example 7
[0139] A) Zn(NO3)3·6H2O and 2,6-di(2,4-dicarboxyphenyl)-4-(phenyl)pyridine were mixed in a molar ratio of 5:2, dissolved in a mixed solvent of water-ethanol-N,N-dimethylformamide (v / v / v=2 / 1 / 5), and mixed evenly until completely dissolved to obtain a solution.
[0140] B) Add a stirring magnet to the solution and place it in a round-bottom flask, connect it to a reflux device, and reflux at 100°C for 24 hours to observe the precipitation of crystals. After cooling to room temperature, take out the mother liquor and sample mixture, filter to obtain a flaky, aggregated crystalline sample. Then, wash it with water and ethanol three times, dry it in a vacuum at 80°C for 2 hours, and then take it out to obtain 21.4 mg of light yellow / yellow-green crystals.
[0141] Example 8
[0142] A) Zn(NO3)3·6H2O and 2,6-di(2,4-dicarboxyphenyl)-4-(phenyl)pyridine were mixed in a molar ratio of 0.2 mmol and 0.05 mmol and dissolved in a mixed solvent of water-ethanol-N,N-dimethylformamide (v / v / v=2 mL / 1 mL / 5 mL), 50 mg of polyvinylpyrrolidone was added, and the mixture was mixed uniformly until completely dissolved to obtain a solution.
[0143] B) Add a stirring magnet to the solution and place it in a round-bottom flask, connect it to a reflux device, and reflux at 100°C for 24 hours to observe the precipitation of crystals. After cooling to room temperature, take out the mother liquor and sample mixture, filter to obtain a flaky, aggregated crystalline sample. Then, wash it with water and ethanol three times, respectively, and vacuum dry it at 80°C for 2 hours, then take it out to obtain 9.8 mg of light yellow / yellow-green crystals.
[0144] The crystal materials obtained in Examples 2-8 were subjected to afterglow luminescence related tests according to the test method in Example 1. The results showed that, similar to Example 1, the crystal materials obtained in Examples 2-8 were observed to emit green afterglow after irradiation with 375nm ultraviolet light for about 30s at 80K, with a spectrum of broadband emission peaks at 500nm to 520nm, a spectrum covering 420nm-700nm, and an afterglow duration of about 6 to 7s. As the ambient temperature increases, the afterglow duration shortens, the afterglow luminescence color gradually turns yellow, and the afterglow spectrum gradually redshifts. According to the corresponding relationship between temperature and afterglow decay time / color, a temperature measurement method based on afterglow decay time / color can be proposed.
[0145] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.
Claims
1. A metal organic framework crystal material, characterized in that: The crystal material is a crystal material having a periodic three-dimensional network structure formed by connecting 2,6-di(2,4-dicarboxyphenyl)-4-(phenyl)pyridine and Zn(Ⅱ).
2. A method for preparing the metal organic framework crystal material according to claim 1, characterized in that: The following steps are involved: A) Preparation of solution: Method 1: Dissolving zinc salt and 2,6-di(2,4-dicarboxyphenyl)-4-(phenyl)pyridine in a solvent to obtain a solution; Method 2: mixing zinc salt, 2,6-bis(2,4-dicarboxyphenyl)-4-(phenyl)pyridine, a solvent and polyvinylpyrrolidone to obtain a solution; B) heat-treating the solution obtained in step A), and then cooling and crystallizing to obtain a metal organic framework crystal material.
3. The preparation method according to claim 2, characterized in that: In step B), the heat treatment temperature is 90-120° C. and the time is 1-5 days.
4. The preparation method according to claim 2, characterized in that: In step A), the zinc salt is at least one of zinc nitrate, zinc sulfate, zinc acetate and zinc chloride.
5. The preparation method according to claim 2, characterized in that: In the first method, the molar ratio of the zinc salt to 2,6-di(2,4-dicarboxyphenyl)-4-(phenyl)pyridine is (1-5):1; In the second method, the molar ratio of the zinc salt to 2,6-di(2,4-dicarboxyphenyl)-4-(phenyl)pyridine is (1-5):
1.
6. The preparation method according to claim 2, characterized in that: In step A), the solvent is a mixed solvent of water and N,N-dimethylformamide, or a mixed solvent of water, ethanol and N,N-dimethylformamide.
7. The preparation method according to claim 6, characterized in that: In the mixed solvent of water and N,N-dimethylformamide, the volume ratio of water to N,N-dimethylformamide is 2:(3-8); In the mixed solvent of water, ethanol and N,N-dimethylformamide, the volume ratio of water, ethanol and N,N-dimethylformamide is 2:1:(3-8).
8. The preparation method according to claim 2, characterized in that: Step B) specifically comprises: heat-treating the solution obtained in step A), cooling it, separating the solid from the liquid to obtain crystals, and then washing and drying them to obtain the metal organic framework crystal material.
9. An application of temperature measurement using a low-temperature long afterglow material, wherein the low-temperature long afterglow material is the metal-organic framework crystal material according to claim 1 or the metal-organic framework crystal material prepared by the preparation method according to any one of claims 2 to 8.
10. The use according to claim 9, characterized in that: The temperature measurement process includes: S1. Establish statistical model: Excite low-temperature long afterglow materials to emit light, record the afterglow decay process at different temperatures, and statistically analyze the corresponding relationship between the indicator and temperature; Wherein, the indicator is afterglow color and / or afterglow decay time; S2, Optical non-contact measurement: The object to be measured is stimulated to emit light, and the obtained indication is compared with the statistical result in step S1 to obtain the corresponding temperature.
Citation Information
Patent Citations
Dual-rare-earth-metal organic frame material used in temperature detection and preparation method of dual-rare-earth-metal organic frame material
CN103319509A
Binary rare earth organic framework crystal material, as well as synthesis method and application thereof
CN106749355A
Ternary rare-earth organic framework crystal material as well as synthesis method and application of ternary rare-earth organic framework crystal material
CN106750350A
Metal-organic framework material for detecting tryptophan, and preparation method thereof
CN107434850A
Preparation of magnetic material-metal organic framework-tyrosinase compound and method for removing phenol by using compound
CN114395551A
Cited By
Preparation method of hydrogen evolution nanoparticle catalyst
CN121538681A